Impact of GDP on Indian AUTO Sector – An analysis of Nifty AUTO Index - Dr. V. Narasimha Rao, Dr. M. Sravani, Mr. Vinayaranjan P (Journal of Informatics Education and Research, 2024)
The capacity of a country to produce products and services determines its economic growth. The Gross National Product (GNP), or Gross Domestic Product (GDP) measures the country's aggregate economic growth. The auto industry is a major engine of India's economic growth. According to the research, it provides 7.1 percent of total GDP and 49 percent of manufacturing GDP, while creating 3.7 crore direct and indirect jobs by the end of 2021. The current study investigates the impact of GDP on the Indian auto sector. It looks for uniformity in the growth rates of the Nifty AUTO and GDP. Information from sources other than the ones under investigation has been obtained for this study, which covers an 11-year period from 2012 to 2022. One-way ANOVA and other descriptive statistics were employed as statistical tools.